Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan - Jen Merlin Tukly; Hadibah Zachra Wadjo; Iqbal Taufik (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Pasal 20 Undang-Undang Number 35 of 2014 explains that those who are obliged and responsible for implementing child protection are the state, government, regional government, community, family, and parents or guardians. For this reason, it is necessary to have child protection which is the business and activities of all levels of society in various positions and roles. The purpose of this research is to explain and discuss forms of legal protection for child victims of violence and their obstacles. The type of research used in this research is normative juridical. With a statutory, case and conceptual approach. The legal sources used are primary, secondary and tertiary. The results of the first study, legal protection for children who are victims of violence can be realized through the provision of restitution and compensation to victims, medical services, and also in the form of legal assistance. Legislative provisions governing the protection of children who are victims of violence are in the Criminal Code, UU number 23 of 2002 concerning child protection, UU Number 23 of 2004 concerning the Elimination of Domestic Violence. against children who are victims of violence occurs due to several factors, namely: (1) lack of human resources; (2) lack of budget by the government; (3) inadequate facilities; (4) victims who find it difficult to ask for information or information because victims still feel afraid, ashamed, and traumatized; (5) the victims' families or relatives did not provide sexual education from an early age and (6) the community did not want to testify in police or court examinations for fear of facing the law.